Social Inequality in the Era of the Digital Economy: A Development Sociology Perspective - Judijanto, Loso; Fadhilah, Nurul (PT. Anagata Sembagi Education, 2026)
The rapid expansion of the digital economy has transformed production systems, labor markets, consumption patterns, and public service delivery. While digitalization is frequently promoted as a driver of inclusion and economic growth, emerging evidence suggests that it also reproduces and restructures social inequality. This study aims to analyze how digital economy transformation generates new forms of stratification from a development sociology perspective and to assess its implications for sustainable and socially just development. The research employs a qualitative design based on a systematic literature review of peer-reviewed studies published between 2021 and 2025. Data were collected through document analysis and examined using thematic analysis and critical interpretative synthesis to identify structural mechanisms linking digital transformation and inequality. The findings indicate that digitalization initially intensifies income polarization due to pro-skill technological bias, regional innovation agglomeration, and concentrated platform ownership. The multidimensional digital divide covering access, capabilities, usage patterns, and governance emerges as a new layer of social stratification. However, under inclusive institutional frameworks, digital finance, entrepreneurship, and adaptive policies can mitigate inequality. The study concludes that achieving sustainable development in the digital era requires a shift from digital equality toward digital justice through redistributive governance and institutional strengthening